Lower limb influence on standing arm-cranking (`grinding`) - Neville, V.; Zaher, N.; Pain, M. T. G.; Folland, J. P. (International Journal of Sports Medicine, 2009)
Standing arm-cranking (`grinding') is predominantly an upper-body exercise, however, the contribution of the legs to this activity is unknown. The purpose of the study was to examine the influence of normal lower-limb movement on physiological strain during arm-cranking. Eight elite professional America's Cup grinders performed two exercise trials, on an adjustable standing arm-crank ergometer with SRM powercrank, in a cross-over design. Each trial comprised of two 5-min stages at the same work rate (~lactate threshold) with the knee joint splinted or normal movement available. Vertical ground reaction forces (VGRF) and knee joint angle were determined from two force plates and sagittal plane video, respectively. Work rate was identical for the two conditions (246 (14) vs. 246 (13) W, p=0.7). Knee joint range of motion and unilateral VGRF amplitude were greater during normal compared with splinted arm-cranking (both p<0.01). There was no difference in VO2 (p=0.2) between the two conditions, however, there was greater VCO2 (8%, p=0.001), RER (11%, p<0.001), VE (17%, p<0.001) and HR (7 (3) beats·min-1, p<0.001) during splinted compared with normal arm-cranking. Furthermore, the rise in BLa was greater after splinted than normal arm-cranking (4.8 (0.8) vs. 3.7 (1.0) mmol/L, p=0.04). These data suggest that the lower-limbs play an integral role in standing arm-cranking, and restricted leg movement markedly affects the cardiovascular and metabolic responses to this activity.